ECOTOURISM VILLAGE AS THE MANIFESTATION OF SOCIAL ENTREPRENEURSHIP - Satrya, I Dewa Gde; Kaihatu, Thomas Stefanus; Pranata, Lexi (Jurnal Entrepreneur dan Entrepreneurship, 2018)
Ecotourism village development uses social entrepreneurship approach. The village has water springs, rivers, conserved forest and its own biodiversity. The involvement of the community to increase the welfare of the community, to grow the sense of belonging and to grow the sense of responsibility to the existence and sustainability of the living environment are important parts of the development of social entrepreneurship. The aim of the research is to describe the implementation of social entrepreneurship in the development of Ecotourism Village. The research is done using qualitative method, by describing the implementation of the science, technology, and art program to Ecotourism Village within the framework of social entrepreneurship. The primary data source is acquired by observation, interview, and focus group discussion. The secondary data source is acquired from relevant references.